A commentary and two responses to: 'What are the effective public schools? Insights from New South Wales' secondary schools using a stochastic frontier analysis with a panel dataset'. Issue 1 (April 2018) - van den Honert, Rob; Dancer, Diane; Blackburn, Vincent; Lietz, Petra
This is a compilation of three items comprising first a commentary on " What are the effective public schools? Insights from New South Wales' secondary schools using a stochastic frontier analysis with a panel dataset " (Diane Dancer & Vincent Blackburn, Australian Journal of Education, 61(2), 2017.https://doi.org/10.1177/0004944117713555 ) followed by two responses to that commentary. The commentary by Rob van den Honert examines whether an appropriate measure of efficiency has been used to interpret the results in this study. He also fields the question: 'is using resources more efficiently more important than achieving superior educational outcomes? In the second item, Diane Dancer and Vincent Blackburn respond to Rob van den Honert's commentary. The third item by Petra Lietz is a brief response to Rob van den Honert's commentary.